Gender, sexuality and reproduction in evolutionary narratives - Oikkonen, Venla (Transformations., 2013)
Since the early 1990s, evolutionary psychology has produced widely popular visions of modern men and women as driven by their prehistoric genes. In Gender, Sexuality and Reproduction in Evolutionary Narratives, Venla Oikkonen explores the rhetorical appeal of evolutionary psychology by viewing it as part of the Darwinian narrative tradition. Refusing to start from the position of dismissing evolutionary psychology as reactionary or scientifically invalid, the book examines evolutionary psychologists' investments in such contested concepts as teleology and variation. The.